Panorama of immigration for Sao Paulo following the Second World War - Salles, Maria do Rosário Rolfsen [UNESP] (My University, 2004)
This article proposes to analyze the results of a research conducted in the São Paulo Immigrants Memorial, whose purpose was to work with an agreement between the state of São Paulo and the Union, according to which the state committed itself to receive, from May 1947 to 1952, immigrants of different European nationalities. Such immigrants had a specific characteristic that conferred them a peculiar status in the eyes of the United Nations, given the fact that they originated from Germany and Austria and where either displaced persons or refugees who could not or did not want to return to their homelands, for several reasons. Italians represented only 0,12% of this group. Italian immigration to Brazil became significant only after 1950, due to the Brazil-Italy immigration agreements.
Keywords: demographic history; immigration; migration determinant; post-war; Brazil; Eastern Hemisphere; Eurasia; Europe; Italy; Sao Paulo [Brazil]; South America; Southern Europe; Western Hemisphere; World